2018
DOI: 10.1371/journal.pone.0204918
|View full text |Cite
|
Sign up to set email alerts
|

The 18F-FDG PET/CT response to radiotherapy for patients with spinal metastasis correlated with the clinical outcomes

Abstract: PurposeTo evaluate the potential role of 18F-fluorodeoxyglucose-positron emission tomography/computerized tomography (FDG-PET/CT) for predicting treatment response after radiotherapy (RT) in patients with spinal metastases.Materials and methodsA retrospective analysis was performed of 42 patients with spinal metastases who received RT from January 2010 to December 2014. All patients underwent FDG-PET/CT before and after treatment. Changes in metabolic responses, expressed as the maximum, mean, peak standardize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, the prognostic value of SUVmax, SUVmean, MATV and TLG for patients with GC remains controversial 55, 56. Both SUVmax and SUVmean can reflect the SUV values of the tumor lesions 55, 57, 58. Although SUVmax and SUVmean are highly correlated, there are still some differences between their prognostic values 55, 57, 58.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prognostic value of SUVmax, SUVmean, MATV and TLG for patients with GC remains controversial 55, 56. Both SUVmax and SUVmean can reflect the SUV values of the tumor lesions 55, 57, 58. Although SUVmax and SUVmean are highly correlated, there are still some differences between their prognostic values 55, 57, 58.…”
Section: Discussionmentioning
confidence: 99%
“…Both SUVmax and SUVmean can reflect the SUV values of the tumor lesions 55, 57, 58. Although SUVmax and SUVmean are highly correlated, there are still some differences between their prognostic values 55, 57, 58. A meta-analysis including eight studies with 1080 patients showed that there was a significant relationship between high SUVmax and poor prognosis, however, the relationship was not significant between SUVmean and poor prognosis 55.…”
Section: Discussionmentioning
confidence: 99%
“…The current analysis is restricted to pre-and post-treatment molecular PET/CT metrics affecting local tumor control. Patients were staged at protocol admission with 18…”
Section: Methodsmentioning
confidence: 99%
“…Youland et al 64 retrospectively evaluated pre‐ and post‐treatment PET‐CT scans in patients with metastatic melanoma treated with SBRT and found that the incidence of flare effect could be significantly reduced when the first scan is performed >2.3 months after SBRT. Using PERCIST criteria, Choi et al evaluated whether changes in PET parameters after treatment with RT for spinal metastases can predict clinical outcomes 65 . They reported that metabolic response to RT, as measured by a change in SUV between baseline and post‐treatment, was predictive of progression‐free survival (PFS) and that a higher residual SUV post‐treatment was associated with a relative resistance to pain relief.…”
Section: Resultsmentioning
confidence: 99%